THE ROLE OF SOCIODRAMA IN ENGLISH SPEAKING CLASS - Berita Mambarasi Nehe (FKIP, Universitas Banten Jaya, 2019)
This study aims to improve the process of students’ speaking skill through sociodrama method on students of English Department of STKIP SetiaBudhiRangkasbitung in Banten region. The participants include 33 students in the third semester. This study uses qualitative descriptive to draw the phenomenon in the classroom when sociodrama applied. Class activity, learning material, class structure in applying sociodrama, student’ perception, sociodrama value, and sociodrama tasks are described to understand the class applied by sociodrama. From the research result, it can be concluded that learning by using sociodrama based task is an effective way and provide students to produce language frequently with the groups and grow student’ motivation well.